2003
DOI: 10.1128/mmbr.67.4.475-490.2003
|View full text |Cite
|
Sign up to set email alerts
|

CcpA-Dependent Carbon Catabolite Repression in Bacteria

Abstract: Carbon catabolite repression (CCR) by transcriptional regulators follows different mechanisms in gram-positive and gram-negative bacteria. In gram-positive bacteria, CcpA-dependent CCR is mediated by phosphorylation of the phosphoenolpyruvate:sugar phosphotransferase system intermediate HPr at a serine residue at the expense of ATP. The reaction is catalyzed by HPr kinase, which is activated by glycolytic intermediates. In this review, the distribution of CcpA-dependent CCR among bacteria is investigated by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(227 citation statements)
references
References 44 publications
3
219
0
2
Order By: Relevance
“…Analysis of the mannose PTS revealed that the genes encoding the EIIABCD Man were consistently highly expressed, regardless of the carbohydrate source (Fig. 1), which is consistent with the important regulatory roles in Gram-positive bacteria established for EII Man (24,25). Similarly, EIIABC Fru seemed consistently highly expressed (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Analysis of the mannose PTS revealed that the genes encoding the EIIABCD Man were consistently highly expressed, regardless of the carbohydrate source (Fig. 1), which is consistent with the important regulatory roles in Gram-positive bacteria established for EII Man (24,25). Similarly, EIIABC Fru seemed consistently highly expressed (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The CCR in L. plantarum NCC245 probably acts through the principal transcriptional regulator CcpA (Warner & Lolkema, 2003), which binds to its operator site, cre. A typical cre element (Miwa et al, 2000) was identified in the rha promoter region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). This cis-acting element (Miwa et al, 2000) is a binding site of the major CCR regulator CcpA (Warner & Lolkema, 2003).…”
Section: Selection Of Bacteria With A-l-rhamnosidase Activitymentioning
confidence: 99%
“…Within EII, EIIA accepts the phosphoryl group from HPr and donates it to EIIB, whereupon EIIC mediates sugar translocation. In addition to controlling sugar translocation, the phosphorylation state of PTS proteins is associated with regulation of metabolic pathways and signaling in bacterial cells (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%